Pengembangan Model Blended Learning Berbasis Literasi Digital dalam Meningkatkan Keterampilan Metakognitif Mahasiswa - Rezki Amelia (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This paper discusses the importance of strengthening digital literacy-based blended learning in improving students' metacognitive skills. The digitalization of technology in the world of education has led to behavioral changes in learning activities, learning resources, and learning models. The application of e-learning using blended learning has an effect on self-regulated learning which is part of meta-cognitive skills. students who are taught using blended learning methods have a higher average of self-regulated learning than students who are taught using traditional internet-based methods. Student learning outcomes who have high self-regulated learning have high learning outcomes, while students who have low self-regulated learning have low learning outcomes